Cryobanking of Fish and Shellfish Egg, Embryos and Larvae: An Overview - Diwan, Arvind D.; Harke, Sanjay N.; Gopalkrishna; Panche, Archana N. (Frontiers in Marine Science, 2020)
Number of attempts have been made to cryopreserve fish and shellfish gametes. Success has been achieved to establish only sperm banks in case of some commercially important fish. In shellfish, also particularly in shrimps, though the sperm cryopreservation was successful, no attempts were made to develop sperm banks. As far as cryopreservation of egg and embryos of fish and shellfish is concerned, less research efforts were made with limited success. Number of reasons have been given for the failure of egg/embryo cryopreservation and the main barriers speculated are low membrane permeability in the eggs, the large yolk mass of the oocyte, and the presence of compartments in early developing embryos. These factors result in ice crystal formation during the freezing process. In addition, the oocytes and embryos are prone to chilling injuries unrelated to ice crystal damage. There are number of other problems reported by several researchers in the egg/embryo cryobanking protocols which are elaborately discussed in the present paper. There is an urgent need to develop a viable cryobanking technology for fish egg/embryos to enhance fish production in captive condition. Attempts to cryopreserve larvae of aquatic animals is another challenge occurring in the recent past. The aim of the present review is to collect comprehensive information on the efforts so far made on fish and shellfish egg and embryo cryobanking; and to assess the challenges in the development of viable technology and plan for future research for making this technology viable and cost effective.